Interview with Steven D. Putzel on Virginia Woolf and the Theater. (Virginia Woolf Miscellany)
An interview with Steven D. Putzel, professor of English and Comparative Literature at Pennsylvania State University--Wilkes Barre, and author of "Virginia Woolf and the Theater" is presented. When asked what led him to women playwrights influenced by the late writer Virginia Woolf, he shares that it was in London, England where he realized that women create and produce theater in more collaborative ways. Putzel explains that his experience as theater audience and reviewer informs the book.